High-performance hafnium oxide-boron nitride composite ceramic as well as preparation method and application thereof
Through the low-temperature in-situ method of pressure-free sintering, the hafnium oxide-boron nitride composite ceramic is used to generate the hafnium oxide-boron nitride composite ceramic, which solves the problem of density of hafnium oxide ceramics and difficulty in sintering hexagonal boron nitride, achieving high Low-temperature preparation and high-temperature application of performance ceramics.
Patent Information
- Application Number
- CN202411264360.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-31
AI Technical Summary
Existing hafnium oxide ceramics are difficult to prepare dense materials through common processes, and high-temperature sintering leads to grain growth, reducing strength and toughness; hexagonal boron nitride ceramics are difficult to sinter and have high high-temperature synthesis costs, and low-temperature in-situ synthesis technology is not yet mature.
Using the pressure-free sintering low temperature in situ method, HfO2, Co, W and amorphous boron powder are used as raw materials, and the blank is made by cold isostatic pressing, and the low temperature is increased in a tube furnace to generate HfO2-x vol%BN-y vol%Co-z vol%W composite ceramics reduce sintering temperature and improve density and mechanical properties.
The low-temperature in-situ preparation of high-performance hafnium oxide-boron nitride composite ceramics is achieved, and dense, high-strength, high toughness and high hardness are obtained. It is suitable for high-temperature environmental components, significantly improving the mechanical properties and application range of the materials.
Smart Images

Figure CN119219413A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic materials, and more specifically, relates to a high-performance hafnium oxide-boron nitride composite ceramic and a preparation method and application thereof. Background Art
[0002] Hafnium oxide (HfO2) is a ceramic material widely used in the field of materials science. It has excellent properties such as high strength, high hardness, wear resistance, and high temperature stability. However, due to the particularity of the material structure, it is difficult to obtain dense materials from hafnium oxide through common process methods. In the preparation process of hafnium oxide ceramics, sintering temperature is one of the important factors affecting its performance.
[0003] The sintering temperature of hafnium oxide ceramics is usually between 1800 and 2000°C, and a higher sintering temperature can produce a denser material. The higher the sintering temperature, the more likely the material will undergo grain growth. Under high temperature conditions, the grains in the material will grow, and the sintered material will have relatively large grains. The larger the grains, the lower the material strength and the worse the toughness. Therefore, a suitable sintering temperature can produce dense, high-strength, and high-toughness hafnium oxide ceramic materials. In addition to the sintering temperature, factors such as sintering time, pressure, and additives will also affect the sintering effect of hafnium oxide ceramics. Among them, the addition of additives can effectively improve the sintering effect of hafnium oxide ceramics, thereby obtaining a denser and more uniform material.
[0004] Hexagonal boron nitride (h-BN) ceramics have a crystal structure similar to that of graphite and are an excellent high-temperature material. They also have the characteristics of low thermal expansion coefficient, high thermal conductivity, thermal shock resistance and corrosion resistance. Therefore, h-BN ceramics have been used in components in high-temperature environments such as crucibles and thermocouple jackets. Literature reports that adding h-BN to ceramics such as oxides and borides will improve the fracture toughness of ceramics, but h-BN ceramics have strong covalent bonds and are difficult to sinter using traditional sintering techniques. Self-propagating high-temperature synthesis (SHS), also known as combustion synthesis, provides an effective method for preparing refractory compounds without using sintering aids. However, the production cost of the ceramics prepared by it is relatively high. The in-situ reaction synthesis (reaction hot pressing) method prepares ceramic composites with good mechanical properties. However, how to achieve low-temperature in-situ synthesis of ceramic composites needs further study. Summary of the invention
[0005] In order to solve the above-mentioned deficiencies and shortcomings of the prior art, a high-performance hafnium oxide-boron nitride composite ceramic is provided, which has high toughness and high hardness.
[0006] Another object of the present invention is to provide a method for preparing the above-mentioned high-performance hafnium oxide-boron nitride composite ceramic. This method is to in-situ generate HfO2-x vol% BN-y vol% Co-z vol% W composite ceramic by pressureless sintering at low temperature.
[0007] Another object of the present invention is to provide an application of the above-mentioned high-performance hafnium oxide-boron nitride composite ceramic.
[0008] The object of the present invention is achieved by the following technical solutions:
[0009] A high-performance hafnium oxide-boron nitride composite ceramic is HfO2-x vol% BN-y vol% Co-z vol% W, where 0 < x ≤ 15, 0 < y ≤ 15, 0 < z ≤ 15; this composite ceramic is prepared by first molding a mixed powder of HfO2, Co, W and amorphous boron powder and then performing cold isostatic pressing at 100-200 MPa to form a green body, filling N2 in a tube furnace, heating to 600-800 °C for heat preservation, and then heating to 1400-1600 °C for heat preservation.
[0010] Preferably, the relative density of the composite ceramic > 99%, the hardness is 30-45 GPa, the fracture toughness is 8-15 MPa·m 1 / 2 , the ceramic grain size is 1-2 μm, and the weight change rate of the composite ceramic after heat treatment at 1500-1800 °C for 1-4 h is 0.2-0.8%.
[0011] Preferably, the purity of the HfO2, Co, W and amorphous boron powder is above 99 wt%, and the particle size of the HfO2, Co, W and amorphous boron powder is 0.1-2 μm.
[0012] Preferably, the molar ratio of the HfO2 to the amorphous boron powder is (1-10):(1-10).
[0013] Preferably, the protective atmosphere is N2.
[0014] The method for preparing the hafnium oxide-boron nitride composite ceramic includes the following specific steps:
[0015] S1. Using HfO2, Co, W and amorphous boron powder as raw materials, adding a solvent and a ball milling medium, mixing on a ball mill, and drying to obtain a mixed powder;
[0016] S2. Molding the mixed powder and then performing cold isostatic pressing at 100-200 MPa to obtain a green body;
[0017] S3. Placing the green body in a tube furnace and filling 1-10 m 3 / minN2, heating to 600-800°C and keeping the temperature, then heating to 1400-1600°C and keeping the temperature, to obtain HfO2-x vol%BN-y vol%Co-z vol%W composite ceramics.
[0018] Preferably, the solvent in step S1 is ethanol, propanol, methanol or acetone.
[0019] Preferably, the mixing time in step S1 is 10 to 24 hours, and the cold isostatic pressing time in step S2 is 5 to 15 minutes.
[0020] Preferably, in step S3, the rate of heating to 600-800°C is 5-10°C / min, the rate of heating to 1400-1600°C is 2-5°C / min, and the insulation time is 0.5-2h.
[0021] The high-performance hafnium oxide-boron nitride composite ceramic is used in components such as crucibles and thermocouple jackets in high-temperature environments.
[0022] The present invention uses HfO2, Co, W and amorphous boron powder as raw materials, and generates HfO2-xvol%BN-yvol%Co-zvol%W composite ceramics in situ by pressureless sintering at low temperature. Since the sintering temperature required for pure HfO2 or BN is relatively high, the addition of Co and W as additives greatly reduces the sintering temperature, and BN is generated in situ, further improving the performance of the hafnium oxide-boron nitride composite ceramics. The appropriate sintering temperature can obtain dense, high-strength, high-toughness hafnium oxide-boron nitride composite ceramics, which can be used in high-temperature environments.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] 1. The present invention uses HfO2, Co, W and amorphous boron powder as raw materials, introduces a protective atmosphere, and uses the amorphous boron powder as a reactant. A part of the amorphous boron powder reacts with nitrogen to generate uniformly distributed BN in situ, and a part of the amorphous boron powder reacts with HfO2 to become HfB2. The grain size of the composite ceramic is finer (1-1.5) μm. W can make up for the reduction of the mechanical properties and high-temperature properties of the hafnium oxide-boron nitride composite ceramic material by the low melting point Co. At the same time, some HfB2 can also be generated, which has a high melting point, high hardness, good corrosion resistance and oxidation resistance, etc., and significantly improves the mechanical properties of the hafnium oxide-boron nitride composite ceramic.
[0025] 2. The present invention adopts a low-temperature in-situ method. The low melting point of Co will greatly reduce the sintering temperature of the hafnium oxide-boron nitride composite ceramic material, improve the sintering performance, and realize the low-temperature (1400-1600°C) in-situ preparation of high-performance hafnium oxide-boron nitride composite ceramics, and also improve the density uniformity and mechanical properties of the composite ceramics, such as wear resistance, strength and hardness.
[0026] 3. The in-situ generated hexagonal boron nitride (BN) of the present invention is an excellent high-temperature material with the characteristics of low thermal expansion coefficient, high thermal conductivity, heat shock resistance and corrosion resistance, which makes its application range wider.
[0027] Description of the attached figure
[0028] Figure 1 The XRD spectra of the hafnium oxide-boron nitride composite ceramics prepared in Examples 1-3 and Comparative Example 1 are shown. DETAILED DESCRIPTION
[0029] The content of the present invention is further described below in conjunction with specific examples, but it should not be construed as limiting the present invention. If not specifically indicated, the technical means used in the examples are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0030] Example 1
[0031] 1. 8.42 g of HfO2 powder (purity 99.3%, particle size 1 μm), 0.47 g of Co powder (purity 99.3%, particle size 1 μm), 0.47 g of W powder (purity 99.3%, particle size 2 μm) and 0.76 g of amorphous boron powder (purity 99.3%, particle size 2 μm) were added to ball milling media Si3N4 balls and propanol solvent and mixed for 23 hours to obtain a mixed powder. The molar ratio of amorphous boron powder to HfO2 was 7:4.
[0032] 2. The mixed powder is cold isostatically pressed at 150 MPa for 5 minutes to obtain a green body;
[0033] 3. Place the blank in a tube furnace and fill it with 5m 3 / min in N2 atmosphere, heated to 650°C at 7°C / min and kept warm for 1.5h, then heated to 1600°C at 3°C / min and kept warm for 1.5h to obtain HfO2-5 vol% BN-5 vol% Co-5 vol% W composite ceramics.
[0034] The relative density of HfO2-5 vol% BN-5 vol% Co-5 vol% W composite ceramics is 99.2%, the hardness is 35 GPa, and the fracture toughness is 10 MPa·m 1 / 2 The grain size is 1.5 μm, and the weight of the ceramic increases by 0.6 wt % after heat treatment at 1600° C. for 2 h. Compared with the HfO2-5 vol% BN-5 vol% Co composite ceramic of comparative example 1, the addition of W improves the performance of the hafnium oxide-boron nitride composite ceramic.
[0035] Example 2
[0036] 1. 14.73 g of HfO2 powder (purity 99.6%, particle size 2 μm), 0.87 g of Co powder (purity 99.6%, particle size 2 μm), 1.73 g of W powder (purity 99.6%, particle size 1 μm) and 0.43 g of amorphous boron powder (purity 99.6%, particle size 1 μm) were added to ball milling media Si3N4 balls and methanol solvent and mixed for 21 hours to obtain a mixed powder. The molar ratio of amorphous boron powder to HfO2 was 4:7.
[0037] 2. The mixed powder is cold isostatically pressed at 100 MPa for 10 min to obtain a green body;
[0038] 3. Place the blank in a tube furnace and fill it with 5m 3 / min in N2 atmosphere, heated to 700°C at 8°C / min and kept warm for 1.5h, then heated to 1500°C at 4°C / min and kept warm for 1.5h to obtain HfO2-5 vol% BN-5vol% Co-10vol% W composite ceramics.
[0039] After adding 10 vol% W, the performance of the hafnium oxide-boron nitride composite ceramic is further improved. The relative density of the HfO2-5 vol% BN-5 vol% Co-10 vol% W composite ceramic is 99.5%, the hardness is 40 GPa, and the fracture toughness is 13 MPa·m 1 / 2 , the grain size is 1.2 μm, and the weight increase of the ceramic after heat treatment at 1700 ° C for 3 h is 0.4 wt%.
[0040] Example 3
[0041] 1. 21.05 g of HfO2 powder (purity 99.9%, particle size 1 μm), 1.31 g of Co powder (purity 99.9%, particle size 2 μm), 3.95 g of W powder (purity 99.9%, particle size 2 μm) and 0.11 g of amorphous boron powder (powder purity 99.9%, particle size 1 μm) were added to ball milling media Si3N4 balls and ethanol solvent and mixed for 24 hours to obtain a mixed powder, the molar ratio of amorphous boron powder to HfO2 was 1:10;
[0042] 2. The mixed powder is cold isostatically pressed at 200 MPa for 15 min to obtain a green body;
[0043] 3. Place the blank in a tube furnace and fill it with 5m 3 / min in N2 atmosphere, heated to 800°C at 10°C / min and kept warm for 2h, then heated to 1400°C at 5°C / min and kept warm for 2h to obtain HfO2-5 vol% BN-5vol% Co-15vol% W composite ceramics.
[0044] Figure 1The XRD patterns of the hafnium oxide-boron nitride composites obtained in Comparative Example 1 and Examples 1-3 are shown in Figure 1. (a) is the HfO2-5 vol% BN-5 vol% Co composite ceramic of Comparative Example 1, (b) is the HfO2-5 vol% BN-5 vol% Co-5 vol% W composite ceramic of Example 1, (c) is the HfO2-5 vol% BN-5 vol% Co-10 vol% W composite ceramic of Example 2, and (d) is the HfO2-5 vol% BN-5 vol% Co-15 vol% W composite ceramic of Example 3. Figure 1 It can be seen that the main phase of the composite ceramics of Comparative Example 1 and Examples 1-3 is HfO2 phase, in addition to BN, Co and HfB2 peaks. This indicates that when N2 is introduced, part of the boron powder reacts with N2 to generate BN phase in situ, and part of the boron powder reacts with HfO2 to generate HfB2 phase in situ, further reducing the sintering temperature. As the W content increases, the peak value of the diffraction peak increases, thereby improving the performance of the hafnium oxide-boron nitride composite ceramics.
[0045] After adding 15 vol% W, the performance of the hafnium oxide-boron nitride composite ceramic is further improved. The relative density of the HfO2-5 vol% BN-5 vol% Co-15 vol% W composite ceramic is 99.9%, the hardness is 45 GPa, and the fracture toughness is 15 MPa·m 1 / 2 , the grain size is 1 μm, and the weight of the ceramic increases by 0.2 wt% after heat treatment at 1800℃ for 4 h. The performance is better after adding higher content of W.
[0046] Comparative Example 1
[0047] 1. Add 2.1g of HfO2 powder (purity 99.9%, particle size 2μm), 0.11g of Co powder (purity 99.9%, particle size 1μm) and 1.08g of amorphous boron powder (purity 99.9%, particle size 2μm), add ball milling media Si3N4 balls and ethanol solvent and mix for 22h to obtain a mixed powder. The molar ratio of amorphous boron powder to HfO2 is 10:1;
[0048] 2. The mixed powder is cold isostatically pressed at 200 MPa for 5 minutes to obtain a green body;
[0049] 3. Place the blank in a tube furnace and fill it with 5m 3 / min protective atmosphere N2, heated to 600°C at 5°C / min and kept warm for 1h, then heated to 1600°C at 2°C / min and kept warm for 1h, to obtain HfO2-5 vol% BN-5 vol% Co composite ceramics.
[0050] The relative density of HfO2-5 vol% BN-5 vol% Co composite ceramic is 99%, the hardness is 30 GPa, and the fracture toughness is 8 MPa·m 1 / 2 , the grain size is 2 μm, and the weight of the ceramic increases by 0.8 wt% after heat treatment at 1500 °C for 1 h.
[0051] The relative density of the composite ceramic of the present invention is greater than 99%, the hardness is 30 to 45 GPa, and the fracture toughness is 8 to 15 MPa·m 1 / 2 The ceramic grain size is 1 to 2 μm. The weight change rate of the composite ceramic after heat treatment at 1500 to 1800° C. for 1 to 4 hours is 0.2 to 0.8%. It has high toughness and high hardness and can be used in the preparation of high-temperature components.
[0052] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principles of the present invention shall be equivalent replacement methods and shall be included in the protection scope of the present invention.
Claims
1. A high-performance hafnium oxide-boron nitride composite ceramic, characterized in that: The composition of the hafnium oxide-boron nitride composite ceramic is HfO2 - x vol% BN - y vol% Co - z vol%, where 0 < x ≤ 15, 0 < y ≤ 15, and 0 < z ≤ 15. The composite ceramic is prepared by first molding a mixed powder of HfO2, Co, W, and amorphous boron powder, followed by cold isostatic pressing at 100 - 200 MPa to form a green body. The green body is placed in a tube furnace, filled with N2, heated to 600 - 800 °C for heat preservation, and then heated to 1400 - 1600 °C for heat preservation.
2. The high-performance hafnium oxide-boron nitride composite ceramic according to claim 1, characterized in that: The relative density of the composite ceramic is greater than 99%, the hardness is 30 to 45 GPa, and the fracture toughness is 8 to 15 MPa·m 1 / 2 The ceramic grain size is 1 to 2 μm, and the weight change rate of the composite ceramic after heat treatment at 1500 to 1800° C. for 1 to 4 hours is 0.2 to 0.8%.
3. The high-performance hafnium oxide-boron nitride composite ceramic according to claim 1, characterized in that: The purities of the HfO2, Co, W, and amorphous boron powder are all above 99 wt%, and the particle sizes of the HfO2, Co, W, and amorphous boron powder are all 0.1 - 2 μm.
4. The high-performance hafnium oxide-boron nitride composite ceramic according to claim 1, characterized in that: The molar ratio of HfO2 to amorphous boron powder is (1 - 10) : (1 - 10).
5. The method for preparing a high-performance hafnium oxide-boron nitride composite ceramic according to any one of claims 1 to 4, characterized in that: It includes the following specific steps: S1. Add HfO2, Co, W, and amorphous boron powder to a solvent and milling media, mill and mix them, and then dry to obtain a mixed powder. S2. Mold the mixed powder and perform cold isostatic pressing at 100 - 200 MPa to obtain a green body. S3. Place the blank in a tube furnace and fill it with 1 to 10 m 3 / min of N2, heating to 600-800°C and keeping the temperature, then heating to 1400-1600°C and keeping the temperature, to obtain HfO2-x vol%BN-y vol%Co-z vol%W composite ceramics.
6. The method for preparing the high-performance hafnium oxide-boron nitride composite ceramic according to claim 5, characterized in that: The solvent in step S1 is one or more of ethanol, propanol, methanol, or acetone.
7. The method for preparing the high-performance hafnium oxide-boron nitride composite ceramic according to claim 6, characterized in that: The mixing time in step S1 is 10 - 24 h, and the cold isostatic pressing time in step S2 is 5 - 15 min.
8. The method for preparing high-performance hafnium oxide-boron nitride composite ceramic according to claim 5, characterized in that: In step S3, the heating rate to 600 - 800 °C is 5 - 10 °C / min, the heating rate to 1400 - 1600 °C is 2 - 5 °C / min, and the heat preservation time for both is 0.5 - 2 h.
9. Use of the high-performance hafnium oxide-boron nitride composite ceramic according to any one of claims 1 - 4 in the preparation of high-temperature components.
Citation Information
Patent Citations
Aluminium oxide, titanium carbide and silicon nitride composite reinforced zirconium boride-based multi-element nano-composite ceramic die
CN104163630A
Aluminium nitride-based multi-element nano-composite ceramic die material and preparation method thereof
CN104163632A
Superfine high-entropy solid solution powder as well as preparation method and application thereof
CN109516812A
High-entropy ceramic with fine grains, high hardness and high toughness as well as preparation method and application of high-entropy ceramic
CN115557793A
High strength ceramic sintered body and its production
JP2001039767A
